Ascorbate Deficiency Can Limit Violaxanthin De-Epoxidase Activity in Vivo - Müller-Moulé, Patricia (American Society of Plant Physiologists, 2002)
As a response to high light, plants have evolved non-photochemical quenching (NPQ), mechanisms that lead to the dissipation of excess absorbed light energy as heat, thereby minimizing the formation of dangerous oxygen radicals. One component of NPQ is pH dependent and involves the formation of zeaxanthin from violaxanthin. The enzyme responsible for the conversion of violaxanthin to zeaxanthin is violaxanthin de-epoxidase, which is located in the thylakoid lumen, is activated by low pH, and has been shown to use ascorbate (vitamin C) as its reductant in vitro. To investigate the effect of low ascorbate levels on NPQ in vivo, we measured the induction of NPQ in a vitamin C-deficient mutant of Arabidopsis, vtc2-2. During exposure to high light (1,500 μmol photons m(−2) s(−1)), vtc2-2 plants initially grown in low light (150 μmol photons m(−2) s(−1)) showed lower NPQ than the wild type, but the same quantum efficiency of photosystem II. Crosses between vtc2-2 and Arabidopsis ecotype Columbia established that the ascorbate deficiency cosegregated with the NPQ phenotype. The conversion of violaxanthin to zeaxanthin induced by high light was slower in vtc2-2, and this conversion showed saturation below the wild-type level. Both the NPQ and the pigment phenotype of the mutant could be rescued by feeding ascorbate to leaves, establishing a direct link between ascorbate, zeaxanthin, and NPQ. These experiments suggest that ascorbate availability can limit violaxanthin de-epoxidase activity in vivo, leading to a lower NPQ. The results also demonstrate the interconnectedness of NPQ and antioxidants, both important protection mechanisms in plants.